A colloidal gold immunochromatography test strip based on a monoclonal antibody for the rapid detection of triadimefon and triadimenol in foods. Issue 1 (1st January 2020) - Lin, Lu; Song, Shanshan; Wu, Xiaoling; Liu, Liqiang; Kuang, Hua
ABSTRACT: In this study, we produced a specific monoclonal antibody (mAb) against triadimefon (TDF) and triadimenol (TDN). The half-maximal inhibitory concentration for TDF and TDN was 5.25 and 9.98 ng/mL, respectively, with a linear detection range (IC20 –IC80 ) of 1.09–25.35 and 2.29–43.61 ng/mL, respectively. Subsequently, we developed a colloidal gold immunochromatography test strip for the analysis of TDF and TDN in tomato. The results obtained from the colloidal gold immunochromatography test strip were in accordance with those obtained from the indirect competitive enzyme-linked immunosorbent assay. The colloidal gold immunochromatography test strip is efficient and suitable for on-site detection of TDF and TDN.